Implementasi ISAK 335 dalam Penyusunan Laporan Keuangan pada Yayasan Insan Muria Bakti Pertiwi Kudus - Mufidatul Auliya; Siti Latifatul Fuadah; Najwa Choirun Nisa’; Ita Rakhmawati (Mafapress Institut Pesantren Mathali'ul Falah Pati, 2026)
This Community Service activity aims to improve the capacity of the Insan Muria Bakti Pertiwi Kudus Foundation management in preparing transparent and accountable financial reports in accordance with Interpretasi Standar Akuntansi Keuangan (ISAK) 335 for non-profit entities. The problem faced by the foundation is a financial recording system that is still simple and does not meet applicable accounting standards. The method used is the Community Based Research (CBR) approach through four stages, namely laying foundation, planning, information gathering and analysis, and acting on finding. This approach allows for identification of needs and the development of solutions in a participatory manner with the foundation management. The results of the activity show an increase in the understanding and skills of the management in implementing ISAK 335, especially in preparing activity reports, reports of changes in net assets, cash flow reports, and statements of financial position more systematically. The application of these standards produces financial information that is more relevant, easy to understand, and can be accounted for to stakeholders, especially donors. This activity concluded that assistance in preparing ISAK 335-based financial reports effectively increases transparency and accountability in the foundation's financial management and supports the sustainability of non-profit organization governance. Going forward, these efforts need to be strengthened through the development of a digital financial reporting system to improve the efficiency and sustainability of organizational management.